Analisis Penggunaan Aplikasi Quizizz Fitur Mode Kertas Sebagai Media Asesmen Formatif Dalam Meningkatkan Hasil Belajar IPAS SD - Nur Andini; Aprilia Shelvi Assholehah; Choirun Nisa; Friska Suudiyah Arifiana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to analyze the use of the Quizizz paper mode feature as a formative assessment medium in improving students’ learning outcomes in the IPAS subject in grade V at SD Negeri Pamolokan 2. The Quizizz paper mode is applied to replace traditional paper tests and provide immediate feedback to students. This research uses a qualitative approach with a case study, involving observation, interviews, and documentation as data collection techniques. The results show that the use of Quizizz paper mode increases student motivation and engagement in formative assessment. The main supporting factor is the availability of devices and a fun learning environment, while the main hindrance is the unstable internet connection. The use of this application simplifies the teacher’s task in evaluating learning and providing quick feedback. Students’ learning outcomes also improved, as they were more motivated to compete in completing the questions and achieving better scores. This study concludes that the Quizizz paper mode feature can be an effective medium for conducting formative assessments to improve student learning outcomes, although technical challenges such as internet connectivity need attention.